Determinants of profitability, company size, managerial ownership and visibility media against disclosure sustainability report - Ramadani, Indy; Purbasari, Heppy (International Journal on Social Science, Economics and Art, 2024)
A sustainability report disclosure is a disclosure made by a company to communicate and disclose its economic, environmental, social, and corporate governance performance, reflecting both positive and negative impacts on stakeholders. This study aims to examine the influence of profitability, company size, managerial ownership, and media visibility on the disclosure of sustainability reports in LQ45 index companies listed on the Indonesia Stock Exchange for the period 2020-2022. This study employs purposive sampling, a technique that selects samples from the population according to predetermined criteria. The study sample consists of 110 samples meeting several criteria, namely being listed on the Indonesia Stock Exchange, publishing a sustainability report, and using GRI standards during 2020-2022. The method of analysis used is multiple linear regression analysis, processed using SPSS software. The results of this study indicate that profitability affects the disclosure of sustainability reports. Meanwhile, company size, managerial ownership, and media visibility do not affect the disclosure of sustainability reports.